The Politics of Civil Society Forms - Muhammad Djindan; Anggalih Bayu Muh. Kamim; Irwan Harjanto (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2021)
Despite the ongoing debate regarding how and to what extent civil society enhances democratic practices, it is generally agreed that there is a reasonable link between civil society and democracy under certain conditions. This paper aims to explore the politics of civil society forms and understand their contribution to the maintenance of democratic practices in Jakarta. Building on a neo-Tocquevillian understanding of civil society, this article analyses urban environmental activists' strategic adoption of voluntary associations and environmental spin-off campaigns as forms of civic engagement to improve public policy. This paper asks how and to what extent these forms of civic engagement provide alternative understandings of civil society's efforts to promote local democracy. We argue that urban environmental activists' spin-off campaigns and voluntary associations represent a particular form of civil society politics, and thus provide different routes to understand local democracy by facilitating diagonal accountability mechanisms. However, further analysis found that the forms adopted by urban environmental activists suffer horizontal and vertical accountability problems similar to those frequently found in more established forms of civil society (e.g. non-government organisations). Nonetheless, the discussion in this paper illustrates civil society's ingenuity in pushing for democratic practices amidst Indonesia's 'democratic recession'.